Flipped Learning: Can Rheumatology Lead the Shift in Medical Education? - El-Miedany, Yaseer; El-Gaafary, Maha; El-Aroussy, Nadia; Youssef, Sally (Current Rheumatology Reviews, 2019)
Objective: To 1. implement flipped classroom rheumatology teaching for undergraduate education. 2. Evaluate outcomes of teaching using OSCE assessment and student perceived effectiveness and satisfaction survey. Methods: The flipped classroom education, 55-students, was conducted in 3 phases. Phase 1: Carried out in the students’ own time. Web links were emailed to assist exposure of the instructional part of the lesson online. Phase 2: Interactive in-class activity to share personal reflection and reinforce the key aspects. Phase 3: A simulated OSCE assessment. A cohort of 56-students, who were taught in the last educational year on the same topics according to standard teaching protocols, were included as control group. The clinical Outcomes were assessed using the scores of the OSCE examination model. Academic outcomes included the engagement measure as well as the students’ answers to perceived effectiveness and satisfaction survey. Results: There was no significant difference regarding demographics between the 2 students’ groups. There was a significant improvement (p< 0.05) in the flipped learning, in contrast to the control group, in terms of clinical (OSCE score) as well as communication skills. Student perceived effectiveness and satisfaction was significantly higher among the flipped learning (p< 0.05). Scores from the flipped learning cohort showed a state of engagement significantly higher than the control group (p< 0.01). Conclusion: Flipped learning implementation musculoskeletal learning successfully demonstrated a promising platform for using technology to make better use of the students' time, and for increasing their satisfaction. Active learning increases student engagement and can lead to improved retention of knowledge.
Keywords: rheumatology